A quantitative analysis of deltoid lengthening and deltoid-related complications after reverse total shoulder arthroplasty: A retrospective case-control study. Issue 2 (March 2020) - Acott, Thomas R.; Brolin, Tyler J.; Azar, Frederick M.; Smith, Richard A.; Throckmorton, Thomas W.
Abstract : Background: Over-lengthening of the deltoid has been hypothesized to increase the risk of specific complications, including acromial fractures, deltoid dehiscence or rupture, and prolonged deltoid pain. We hypothesized that progressive deltoid lengthening would be associated with an increasing number of these complications and that there would be a threshold of deltoid length beyond which these complications would be more common. Methods: After database review, three patient cohorts were established for comparison: nine patients with deltoid-related complications (acromial fractures and deltoid dehiscence) and four with persistent deltoid pain and/or tightness that persisted at least 2 yr postoperatively; these were matched with a 1:2 control group drawn from the same database (26 patients without these complications). Results: The overall average deltoid lengthening was 20.6 mm. For patients with acromial fractures or deltoid dehiscence, the length averaged 28.5 mm; for patients with persistent deltoid pain, the average length was 26.3 mm; and for controls, the length was 17.0 mm. Conclusions: Sufficient deltoid tensioning is vital to the stability of a reverse prosthesis as well as patient range of motion and outcomes; however, increased deltoid lengthening during reverse total shoulder arthroplasty increases the risk of postoperative tension-related complications. These data suggest that lengthening more than 26 mm is a risk factor for deltoid-related complications after reverse total shoulder arthroplasty. Level of Evidence: Level III.